Eco-art therapy in practice - Pike, Amanda Alders (New York, NY : Routledge, 2021)
"Eco-Art Therapy in Practice is uplifting, optimistic, and empowering while outlining cost-effective, time efficient, and research-based steps on how to use nature in session to enhance client engagement and outcomes. This text will help clinicians and educators to employ eco-art therapy in practice, in turn empowering their clients and conveying an inclusive message of respect- respect for self, others, community, and the world"--
OCLC-licensed vendor bibliographic record.
Keywords: Art therapy; Ecology in art; Nature -- Therapeutic use; PSYCHOLOGY / Psychotherapy / General